Features of regression of different stages of retinoblastoma after primary combined (intravitreal plus systemic) polychemotherapy and additional consolidation therapy - Nadiya Bobrova; Svitlana Tronina; Tetyana Sorochynska; Tetyana Romanova; Ganna Dembovetska; A.V. Shylyk; O.D. Dovgan (Ukrainian Society of Ophthalmologists, 2023)
Background: Complete retinoblastoma (RB) regression is defined as final changes undergone by the tumor in the course of eye-salvage treatment. Studies of RB regression patterns following various types of eye-salvage treatment are important for assessing the outcomes of this treatment. Purpose: To study the regression patterns in different stages of RB after primary combined polychemotherapy (PCPC) and additional consolidation therapy. Material and Methods: We reviewed RB regression patterns in 89 children (119 eyes) aged 1.5 to 77 months after PCPC and various types of consolidation therapy. Of these children, 37 had unilateral retinoblastoma, and 52, bilateral retinoblastoma. At presentation, T3 RB was the most prevalent (67.2%), followed by T2 (23.6%). T1 stage was observed only in 9.2% - most often it was diagnosed on a fellow "healthy" eye at a spreading T3 stage of the countralateral eye. Sixteen eyes (13%) had multifocal tumors type of tumor growth. Because the number of tumor foci per eye ranged from one to three, the total number of foci (124) exceeded the total number of affected eyes. Treatment was carried out according to the developed PСPС method, which invсcluded the intravitral injection of melfalan at the dose of 10-30 mcg, depending on the tumor stage, followed by intravenous systemic therapy (VEC protocol). Results: We found different RB regression patterns after PCPC. After the first cycle of PCPC, type 2 regression pattern was typical for small T1 tumors, whereas type 3 regression pattern was most prevalent (60%) for T2 and T3 tumors. This is likely to indicate tumor mosaicism with the presence of less differentiated and, consequently, more malignant cell types, which faster reacted to PCPC by calcification than surrounding more differentiated and, consequently, less malignant cells which reacted weaker. After the completion of PCPC, type 1 regression pattern was seen in 29%, which indicated complete regression, whereas type 3 regression pattern persisted in 33% foci. The features of tumor regression following PCPC included (a) fragmentation of a large RB (59.3%) after first 1-2 PCPC cycles with appearance of necrotic foci which resolved or calcified finally; (b) presence of various types of regression in one eye in the multifocal growth; and (c) transformation of a regression type into another regression type: most commonly, transformation of type 2 into type 3 and type 3 into type 1.